Influência da incorporação de aditivos nas propriedades do Poli (Hidroxibutirato-co-hidroxivalerato) - PHBV - Brunel, Daiane Gomes (Universidade Federal de São Carlos, 2008)
The concept of environmentally correct products has been exhaustively discussed and, today, the use of biodegradable polymers appears as a feasible alternative for the problem of inadequate disposal of plastic waste products. Poly(hydroxybutyrate) PHB and the copolymer poly(hydroxybutyrate-cohydroxyvalerate) PHBV are among the main members of the class of biodegradable polymers, which are thermoplastic polymers produced from a renewable source and 100% biodegradable. However, PHB and PHBV still present several limitations, such as stiffness and brittleness, low thermal stability, and a narrow process window. However, the thermal and mechanical performance of PHB and PHBV can be improved through the use of additives. In view of this fact, the objective of this study was to produce materials with properties optimized through the incorporation of a plasticizer, nucleant and thermal stabilizer to the PHBV copolymer. The formulations were subjected to the following tests: tensile and notched Izod impact tests, melt flow index, differential exploratory calorimetry (DSC) and thermogravimetry (TG). Additivation of the copolymers proved effective, usually resulting in adequate processability due to the presence of the nucleant and the improved physicomechanical properties provided by the plasticizer. The thermal stabilizer proved dispensable since the stability of the PHBV was not improved. A comparison was made of the results obtained in some properties for the two copolymers with different hydroxyvalerate contents. The copolymer containing more HV proved better than the other, even displaying greater compatibility with the most efficient additives. The biodegradability was evaluated based on mass loss, alterations in the mechanical tensile properties, and SEM analysis after 180 days in organic soil. The additivated formulations presented higher mass loss than the pure copolymer, indicating the feasibility of producing a copolymer with adequate physical and mechanical properties combined with the desired biodegradability.
Influence of additives incorporation on the properties of Poly(Hydroxybutyrate-co-hydroxyvalerate) PHBV
Keywords: Poli (Hidroxibutirato-co-hidroxivalerato) - PHBV; Aditivos; Polímeros biodegradáveis; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA